The Evolution of the "Gypsy" Female Character in Mexican Cinema (1943--1978) and its race and nationalist implications - Sabino-Salazar, Mariana (Romano džaniben, 2021)
In this article I analyze the Gypsy femme fatale archetype in twenty-seven films that go from 1943 to 1978. I aim to answer the following questions: how was the character of the Gypsy woman in Mexican cinema influenced by European literary archetypes and how has this figure evolved? What are the political implications of female Gypsy characters for racial and national symbolic systems? I will review gradual changes in the Gypsy stereotype from "the White Spanish girl kidnapped and raised as a Gypsy" found in Spanish literature to the "eerie Eastern European Vamp" found in Gothic narratives. Perhaps the most common form of the stereotype was "La Petenera", a realization of the fantasy of the sexually aggressive woman. The archetype of an attractive and dangerous nomad was a reaction to a recurring unease, a trope long embedded in literature, cinema, music, and popular culture on both sides of the Atlantic.
Keywords: stereotypes; cinema; race; Mexico; nationalism; the Gypsy image